The social significance of AI in retail on customer experience and shopping practices. (January 2022) - Moore, Simon; Bulmer, Sandy; Elms, Jonathan
Abstract: This paper draws on practice-informed, ethnographic research to develop an understanding of the novel social consequences and opportunities afforded from consumers' interactions with AI digital humans as part of the in-store shopping experience. We reveal and interrogate consumers' experiences with AI digital humans in an exploratory study undertaken during the launch phase of an in-store kiosk digital store greeter in a flagship store of a large national technology and appliance chain. Our findings contribute to understanding the social significance of AI in retail on customer experience (CX) and the managerial implications of consumers interactions with AI digital humans are described and discussed.